Steel material for rib plate and production method thereof
By optimizing the content of carbon and manganese and the ratio of other elements, combined with advanced smelting and heat treatment processes, steel for ribbed plates with high strength, toughness and corrosion resistance are prepared, which solves the shortcomings of traditional carbon steel in multiple properties and meets the high standards of modern engineering.
Patent Information
- Application Number
- CN202411965442.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
Traditional ordinary carbon steel is insufficient in terms of high strength, high toughness, corrosion resistance, lightweight and process stability, making it difficult to meet the multiple needs of modern engineering for building materials.
By optimizing the content range of carbon and manganese (carbon 0.12% to 0.18%, manganese 0.8% to 1.2%), combining the reasonable proportion of elements such as silicon, phosphorus, sulfur, aluminum, chromium, nickel, copper, etc., the steel for ribs with high strength, toughness and corrosion resistance is prepared by oxygen converter smelting, continuous casting, normalization, tempering and low-temperature oxidation treatment.
It achieves the best balance of strength, toughness and wear resistance of steel, significantly improves service life and corrosion resistance in complex environments, and meets the high standards requirements of modern engineering for building materials.
Smart Images

Figure CN119753506A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steel materials, in particular to a steel material for rib plates and a production method thereof. Background Art
[0002] As the industrialization process continues to accelerate, the application scenarios of building materials are becoming increasingly complex, and the performance requirements for steel have far exceeded traditional standards. Modern engineering has put forward the following multiple requirements for building materials: high strength, high toughness, corrosion resistance, lightweight and cost-effectiveness. However, traditional ordinary carbon steel has obvious deficiencies in these key performance indicators and is difficult to meet the high standards of current engineering practice.
[0003] However, the production method of steel for ribbed plates in the prior art has the following defects: Carbon steel has long been widely used in structural materials such as building ribs due to its low cost and good machinability. However, in the chemical composition design of traditional ordinary carbon steel, the ratio of carbon (C) and manganese (Mn) is relatively simple, usually with a carbon content of less than 0.10% and a manganese content of less than 0.6%. Although this composition design can meet basic strength requirements, it has poor adaptability to high-load and high-strength environments; Building ribs are usually exposed to complex environments for a long time, including high humidity, acid and alkali corrosion, salt spray and other harsh conditions. Traditional ordinary carbon steel lacks corrosion-resistant elements (such as chromium, nickel, and copper), and its corrosion resistance depends on surface coatings or external protective treatments rather than the corrosion resistance of the substrate itself.
[0004] Traditional carbon steel production processes are usually relatively simple, making it difficult to balance performance improvement and cost control. For example, existing carbon steel heat treatment processes usually remain at the level of normalizing or simple tempering, and fail to perform system optimization based on performance requirements; Lightweighting of building materials is an important trend in the development of modern engineering, especially in the fields of high-rise buildings and bridge structures. Reducing the weight of materials can significantly reduce loads and construction difficulties. However, due to strength limitations, traditional carbon steel often needs to increase the section thickness to meet safety standards, which contradicts the lightweight requirements. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a steel material for rib plates and a production method thereof, which solves the shortcomings of traditional carbon steel in high strength, high toughness, corrosion resistance, light weight and process stability, especially the problem that it is difficult to meet modern engineering needs under complex environments and high load conditions.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: A steel material for rib plates, comprising: Carbon: 0.12%~0.18% Carbon is one of the main strengthening elements of steel. Its content is in the range of 0.12% to 0.18%, which can improve the strength of steel while maintaining good toughness and welding performance. Too high carbon content will increase the brittleness of steel, while too low carbon content cannot guarantee strength. This range takes into account strength, toughness and processing performance; Manganese: 0.8% to 1.2% Manganese can significantly increase the strength and hardness of steel and improve its hot working properties. Manganese forms manganese carbide with carbon, further improving the wear resistance of steel. The content range is 0.8% to 1.2%, which can effectively inhibit the adverse effects of sulfide inclusions on steel properties while maintaining the toughness and weldability of steel.
[0007] Silicon: 0.10% to 0.25% Silicon acts as a deoxidizer in steel and can also improve the strength and corrosion resistance of steel. The content range is 0.10% to 0.25%, which ensures strength and toughness while avoiding the adverse effects of excessive silicon on the plasticity and processing properties of steel.
[0008] Phosphorus: ≤0.03% The phosphorus content is strictly controlled at ≤ 0.03% to avoid its adverse effect on the impact toughness of the steel while improving the low temperature performance.
[0009] Sulfur: ≤0.025% Sulfur easily forms brittle inclusions in steel, reducing toughness. By controlling the sulfur content to ≤0.025%, the processing performance and mechanical properties of steel can be improved.
[0010] Aluminum: ≥0.015% As an effective deoxidizing element, aluminum can promote grain refinement and improve the toughness of steel. When the aluminum content is ≥0.015%, it can significantly improve the purity of steel during the smelting process and reduce the impact of inclusions.
[0011] Chromium (Cr): 0.06% to 0.1% Chromium improves the corrosion resistance of steel by forming a dense Cr2O3 oxide film. It also improves the hardenability during heat treatment and reduces the risk of heat treatment deformation and cracking of steel.
[0012] Nickel (Ni): 0.05% ~ 0.1% Nickel can refine the grain size, increase the strength and toughness of steel, and further improve hardenability when coexisting with chromium, that is, during heat treatment, the steel can harden evenly, reducing the risk of deformation and cracking.
[0013] Copper (Cu): 0.05% to 0.1% Copper in steel can significantly improve the steel's resistance to atmospheric corrosion, especially in high humidity environments.
[0014] The rest is iron: 97.5% to 98.8%.
[0015] Iron, as a matrix component, provides the basis for steel's strength and toughness.
[0016] Preferably, the content of chromium, nickel and copper is ≤0.3%.
[0017] A method for producing steel for rib plates comprises the following steps: (1) Raw material preparation: preparing the chemical composition according to claim 1; (2) Smelting: using oxygen converter to obtain molten iron; (3) Continuous casting: Molten iron is cast into a slab and then cooled; (4) Normalizing: heating the ingot for normalizing, followed by natural cooling in air; (5) Tempering: heating the ingot for tempering and then cooling; (6) Surface treatment: The surface of the ingot is treated by low temperature oxidation treatment in a low temperature oxidation environment of 150-200°C for 12 hours.
[0018] Preferably, an aluminum deoxidizer is added during the smelting process, and the amount of the deoxidizer added is 0.02% to 0.05%.
[0019] Preferably, the oxygen converter temperature is 1600-1650°C, and the vacuum degassing pressure is 100-110 Pa. The oxygen converter rapidly melts molten iron at high temperature and removes harmful impurities (such as sulfur and phosphorus). Aluminum, as a deoxidizer, can react with oxygen to form Al2O3 inclusions, reduce the oxygen content in steel, prevent the formation of pores and inclusions, and improve the purity of steel.
[0020] Preferably, during the continuous casting, the molten iron flow rate is 1.2-1.5 m / s, and the cooling rate is 2.5-3.5° C. / s.
[0021] Controlling the molten iron flow rate and cooling rate during the continuous casting process can avoid cracks and segregation in the ingot, ensure internal composition uniformity and dimensional accuracy, and lay the foundation for subsequent heat treatment.
[0022] Preferably, during the normalizing treatment, the ingot is heated to 900-950° C. and the holding time is 40-60 min.
[0023] Normalizing can refine the grains, improve the toughness and strength of steel, and reduce residual stress during processing. A uniform austenite structure is formed within this temperature range and transforms into fine pearlite and ferrite structures during cooling.
[0024] Preferably, in the tempering treatment, the ingot is heated to 300-500°C, kept at this temperature for 23-23.5h, and cooled at a rate of 0.5-1.5°C / min.
[0025] Tempering can release the residual stress inside the steel and improve its toughness and plasticity. The tempering temperature range is controlled at 300-500℃, which can adjust the tempered martensite structure and optimize the mechanical properties.
[0026] Preferably, a low temperature oxidation furnace is used to perform surface treatment on the ingot, and the surface treatment comprises the following steps: Clean the surface of the ingot after tempering to remove grease, oxide scale and impurities on the surface; Placing the cleaned ingot into the heating zone of the low temperature oxidation furnace; Connect oxygen and start the low-temperature oxidation furnace, raise the temperature in the furnace to 150-200°C at a heating rate of 3-5°C / min, maintain the temperature for oxidation treatment for 11.5-12.5 hours, continuously supply oxygen during the period, the oxygen flow rate is 10-20L / min, and the oxygen purity is ≥99.9%; after completion, turn off the heating system, control the cooling rate to 2-5°C / min and cool to room temperature; After cooling to room temperature, the surface of the ingot is purged to remove floating ash and loose oxide particles.
[0027] Preferably, when the ingots are placed, a gap of 20 to 30 mm is left between two adjacent ingots for oxygen circulation.
[0028] Low temperature oxidation treatment forms a dense oxide film (mainly Cr2O3 and NiO) on the surface of steel by controlling the temperature and oxygen environment, which significantly improves the corrosion resistance and prevents the oxide layer on the surface of steel from falling off or cracking. Controlling the cooling rate and purging process can ensure the uniformity and stability of the oxide film.
[0029] The present invention provides a steel material for rib plates and a production method thereof. The steel material has the following beneficial effects: 1. The present invention achieves the best balance among the strength, toughness and wear resistance of steel by controlling the carbon and manganese contents through adopting the technical solution of optimizing the addition ratio of carbon and manganese. Compared with the technical solutions in the prior art in which the carbon content is too high, resulting in increased brittleness of steel and decreased processing performance, or the carbon content is too low, resulting in insufficient strength, the present invention solves the problem of limited mechanical properties of steel and provides performance support for the application of ribbed plate steel in high-load structures.
[0030] 2. The present invention adopts the technical solution of synergistic addition of chromium, nickel and copper, and significantly enhances the service life of steel in complex corrosive environments by forming a dense Cr2O3 oxide film with chromium, refining grains with nickel to generate carbides, synergistically improving hardenability and corrosion resistance with nickel and chromium, and improving atmospheric corrosion resistance with copper. Compared with the technical solution in the prior art that fails to take into account both mechanical properties and corrosion resistance by adding a single corrosion-resistant element, the present invention solves the technical problem of insufficient performance of steel in high humidity or chemical corrosion environments.
[0031] 3. The present invention adopts a low-temperature oxidation treatment technical solution to generate dense Cr2O3 and NiO oxide films on the surface of steel, which significantly improves the corrosion resistance and surface hardness of the steel. Compared with the technical solution of high-temperature oxidation treatment in the prior art that causes uneven or easy-to-peel oxide films, the present invention solves the problem of insufficient stability of the steel surface protective layer in complex corrosion environments.
[0032] 4. The present invention adopts a heat treatment technology solution combining normalizing and tempering, refines grains by normalizing, makes the structure uniform, and eliminates residual stress by tempering, thus significantly improving the toughness, plasticity and fatigue resistance of steel. Compared with the technical solutions in the prior art that only rely on high-temperature normalizing or single tempering treatment, which leads to grain coarsening or difficulty in releasing internal residual stress, the present invention solves the problem of unstable steel structure performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a flow chart of the production method of the present invention. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] In order to better understand the present invention, the above contents are described in detail below in conjunction with specific embodiments. Please see attached Figure 1 Embodiment 1: Method for producing steel material for rib plate with preferred mechanical properties Implementation steps 1. Raw material preparation Ingredients: Carbon (C): 0.15%, Manganese (Mn): 1.0%, Silicon (Si): 0.2%, Phosphorus (P): 0.025%, Sulfur (S): 0.02%, Aluminum (Als): 0.02%, Chromium (Cr): 0.08%, Nickel (Ni): 0.08%, Copper (Cu): 0.07%. The rest is iron, impurity content ≤ 0.02% 2. Smelting The above ingredients are added into an oxygen converter, the furnace temperature is controlled at 1650°C, and aluminum deoxidizer (the addition amount is 0.03%) is added at the same time for deoxidation and de-doping treatment.
[0036] The vacuum degassing treatment was performed under vacuum conditions with the pressure controlled at 105Pa to remove dissolved gases (such as oxygen, nitrogen and hydrogen).
[0037] After tapping, the temperature of the molten steel is maintained at 1520°C.
[0038] 3. Continuous casting The molten steel was cast at a flow rate of 1.3 m / s, and the cooling rate was controlled at 3.0°C / s to form a cast billet with a thickness of 200 mm.
[0039] 4. Normalizing The ingot was heated at 950°C, kept at that temperature for 50 minutes, and then naturally cooled to room temperature in air.
[0040] 5. Tempering The ingot was heated to 350°C for 23.5 hours and the cooling rate was controlled at 1.0°C / min.
[0041] 6. Surface treatment The surface of the tempered ingot is cleaned to remove grease, scale and impurities, and then placed in a low-temperature oxidation furnace.
[0042] The heating rate was 4°C / min, the temperature was raised to 180°C, and the oxidation treatment time was maintained for 12 hours. The oxygen flow rate was 15 L / min, and the oxygen purity was 99.9%.
[0043] The cooling rate was controlled at 3°C / min, and after cooling to room temperature, cold air was blown for 8 minutes.
[0044] Summary of Examples This embodiment significantly improves the mechanical properties of the steel by precisely controlling the ratio of carbon and manganese and process parameters. The test results are as follows: Yield strength: 340MPa Tensile strength: 480MPa Elongation: 26% At the same time, the corrosion resistance is enhanced through surface treatment, and the oxide film is dense and uniform without peeling.
[0045] Logical analysis: In this embodiment, the optimization of carbon and manganese content realizes the formation of manganese carbide, effectively strengthening the steel matrix structure. At the same time, normalizing and tempering treatments refine the grain structure, further improving the strength and toughness. The precise control of surface treatment time and oxidation temperature ensures the balance of corrosion resistance, so that the steel exhibits excellent mechanical properties and corrosion resistance.
[0046] Example 2: Method for producing steel material for rib plate with preferred corrosion resistance Implementation steps 1. Raw material preparation Ingredients: Carbon (C): 0.12%, manganese (Mn): 0.9%, silicon (Si): 0.15%, phosphorus (P): 0.02%, sulfur (S): 0.015%, aluminum (Als): 0.02%, chromium (Cr): 0.1%, nickel (Ni): 0.1%, copper (Cu): 0.1%. The rest is iron, and the impurity content is ≤ 0.02%.
[0047] 2. Smelting The smelting is carried out in an oxygen converter, the furnace temperature is maintained at 1600°C, an aluminum deoxidizer (0.05%) is added, and vacuum degassing treatment is carried out at the same time, and the pressure is controlled at 105Pa.
[0048] 3. Continuous casting The flow rate of molten steel was controlled at 1.4 m / s, the cooling rate was 3.5 °C / s, and ingots with a size of 250 mm were cast.
[0049] 4. Normalizing The ingot was heated to 920°C, kept at that temperature for 60 minutes, and then naturally cooled to room temperature in air.
[0050] 5. Tempering Heat to 400°C, keep warm for 3 hours, and cool at a rate of 1.5°C / min.
[0051] 6. Surface treatment Low-temperature oxidation treatment: After cleaning the surface of the ingot, place it in a low-temperature oxidation furnace with a heating rate of 3°C / min, an oxidation temperature of 150°C, an oxidation time of 11.5 hours, and an oxygen flow rate of 12 L / min.
[0052] The cooling rate was 2.5°C / min, and after cooling to room temperature, cold air was blown (for 5 minutes).
[0053] Summary of Examples This embodiment takes the synergistic effect of chromium, nickel and copper as the core to improve the corrosion resistance of steel. The test results are as follows: Corrosion potential: Increased by 150mV Corrosion current density: reduced by 20% Yield strength: 330MPa Tensile strength: 470MPa The corrosion resistance is significantly improved, suitable for hot, humid and corrosive environments.
[0054] Logical analysis: Compared with Example 1, this example slightly increases the content of chromium, nickel and copper, thereby enhancing the compactness of the surface oxide film and improving the corrosion resistance. However, due to the low content of carbon and manganese, the mechanical strength is slightly reduced.
[0055] Example 3: Production method of steel for rib plate with preferred process stability Implementation steps 1. Raw material preparation Ingredients: Carbon (C): 0.18%, manganese (Mn): 1.1%, silicon (Si): 0.25%, phosphorus (P): 0.02%, sulfur (S): 0.02%, aluminum (Als): 0.025%, chromium (Cr): 0.07%, nickel (Ni): 0.08%, copper (Cu): 0.08%. The rest is iron, and the impurity content is ≤ 0.02%.
[0056] 2. Smelting The steel was smelted at 1650°C in an oxygen converter, an aluminum deoxidizer (0.03%) was added, and vacuum degassing was performed at a pressure of 105 Pa.
[0057] 3. Continuous casting The casting flow rate is 1.5 m / s, the cooling rate is 2.8 °C / s, and the ingot size is 200 mm.
[0058] 4. Normalizing Heat to 950°C, keep warm for 40 minutes, and cool naturally in air.
[0059] 5. Tempering Heating to 500°C, holding time for 2 hours, cooling rate of 1.0°C / min.
[0060] 6. Surface treatment After cleaning, the ingot was placed in a low-temperature oxidation furnace with a heating rate of 5°C / min, an oxidation temperature of 200°C, an oxidation time of 12 hours, and an oxygen flow rate of 20 L / min.
[0061] The cooling rate was 3°C / min, and the purge time after cooling was 10 minutes.
[0062] Summary of Examples This embodiment focuses on optimizing the stability of production process parameters to ensure the balanced performance of steel in terms of mechanical properties and corrosion resistance. The test results are as follows: Yield strength: 360MPa Tensile strength: 500MPa Elongation: 24% The surface oxide film is uniform and has excellent corrosion resistance.
[0063] Logical analysis: Due to the high ratio of carbon and manganese in this embodiment, and the optimization of normalizing and tempering parameters, the mechanical properties are maximized, while the corrosion resistance is maintained well. The stability of process control makes the final performance balanced, which is suitable for large-scale industrial applications.
[0064] Comprehensive logic analysis Example 1 highlights the optimized ratio of C and Mn, and performs best in mechanical properties while maintaining certain corrosion resistance.
[0065] Example 2 enhances the corrosion resistance by increasing the proportion of chromium, nickel and copper, but the mechanical properties are slightly lower than those of Example 1.
[0066] Example 3 finds a balance between mechanical properties and corrosion resistance, while optimizing process stability to make the production process suitable for industrial applications.
[0067] Through the optimization schemes of different embodiments, the effect of the present invention on solving the performance deficiencies in the background technology is fully demonstrated.
[0068] Comparative Example 1: No optimization of the ratio of carbon and manganese process: Raw material preparation Ingredients: Carbon (C): 0.10%, Manganese (Mn): 0.6%, Silicon (Si): 0.2%, Phosphorus (P): 0.03%, Sulfur (S): 0.02%, Aluminum (Als): 0.02%, Chromium (Cr): 0.08%, Nickel (Ni): 0.08%, Copper (Cu): 0.07%.
[0069] The rest is iron, with an impurity content of 0.02%.
[0070] Production method The production is carried out according to the process flow of Example 1, which specifically includes smelting, continuous casting, normalizing, tempering and surface treatment.
[0071] Comparison results Performance Test: Yield strength: 280MPa Tensile strength: 400MPa Elongation: 18% analyze: The low carbon content leads to insufficient carbide formation, reducing the strengthening effect of the matrix; the too low manganese content fails to fully improve the hardness and toughness of the steel.
[0072] Compared with Example 1, the mechanical properties of this comparative example are significantly reduced, indicating that optimizing the ratio of carbon to manganese is the key to achieving high strength and high toughness.
[0073] Comparative Example 2: No addition of chromium, nickel, and copper synergistic elements process: Raw material preparation Ingredients: Carbon (C): 0.15%, Manganese (Mn): 1.0%, Silicon (Si): 0.2%, Phosphorus (P): 0.025%, Sulfur (S): 0.02%, Aluminum (Als): 0.02%.
[0074] No added chromium, nickel or copper.
[0075] The rest is iron, with an impurity content of 0.02%.
[0076] Production method The production is carried out according to the process flow of Example 2, including smelting, continuous casting, normalizing, tempering and surface treatment.
[0077] Comparison results Performance Test: Corrosion potential: -0.55V Corrosion current density: increased by 30%.
[0078] The surface hardness decreased by about 10%.
[0079] analyze: Without adding chromium, nickel and copper, a dense oxide film cannot be formed on the surface, and the corrosion resistance is significantly reduced. The reduction in surface hardness further illustrates the key role of synergistic elements.
[0080] Compared with Example 2, this comparative example cannot meet the use requirements in hot and humid and corrosive environments, highlighting the necessity of the coordinated addition of chromium, nickel and copper.
[0081] Comparative Example 3: Normalizing temperature is too high process: Raw material preparation The ingredients are consistent with those in Example 1.
[0082] Normalizing The normalizing temperature was set to 1000° C. and kept at this temperature for 50 minutes. The remaining processes were the same as those in Example 1.
[0083] Comparison results Performance Test: Yield strength: 320MPa Tensile strength: 450MPa Elongation: 20% analyze: Too high normalizing temperature causes grain coarsening, which weakens the strength and toughness of the steel.
[0084] Compared with Example 1, the mechanical properties in this comparative example are reduced, indicating that the optimization of normalizing temperature (950°C) is crucial to grain refinement and performance improvement. Comparative Example 4: Insufficient surface treatment process: Raw material preparation The ingredients are consistent with those in Example 2.
[0085] Surface treatment The oxidation temperature was controlled at 140° C., the oxidation time was shortened to 6 hours, and the other processes were consistent with Example 2.
[0086] Comparison results Performance Test: Corrosion potential: -0.48V Corrosion current density: increased by about 15%.
[0087] The surface oxide film is uneven and peeling occurs in some areas.
[0088] analyze: The surface treatment temperature is too low and the time is insufficient, so the oxidation reaction is not complete, resulting in insufficient density and uniformity of the oxide film.
[0089] Compared with Example 2, the corrosion resistance of this comparative example is significantly deteriorated, proving that the optimization of the surface treatment process parameters (180° C., 12 hours) is the key to achieving excellent corrosion resistance.
[0090] Comparative Example 5: Tempering temperature is too low process Raw material preparation The ingredients are consistent with those in Example 3.
[0091] Tempering The tempering temperature was set to 250° C. and kept warm for 2 hours. The remaining processes were consistent with those in Example 3.
[0092] Comparison results Performance Test: Yield strength: 360MPa Tensile strength: 480MPa Elongation: 18% analyze: Too low tempering temperature leads to insufficient release of internal residual stress, decreased plasticity and significantly reduced elongation.
[0093] Compared with Example 3, this comparative example verifies the necessity of optimizing the tempering temperature (500°C) to improve plasticity and toughness.
[0094] Comparative Example Summary Through the above five comparative example experiments, the innovation and improvement effect of the embodiments of the present invention are fully verified: Comparative Example 1: This shows the key role of optimizing the ratio of carbon to manganese in improving mechanical properties.
[0095] Comparative Example 2: Highlights the importance of synergistic addition of chromium, nickel and copper for improving corrosion resistance.
[0096] Comparative Example 3: Verify that the optimization of normalizing temperature can refine the grains and avoid the decrease of strength and toughness.
[0097] Comparative Example 4: It shows that the optimization of surface treatment parameters is crucial to improving the density and corrosion resistance of the oxide film.
[0098] Comparative Example 5: Reveals the decisive influence of tempering temperature on releasing residual stress and improving plasticity.
[0099] By comparing the embodiments with the comparative examples, the improvement effects of the present invention on mechanical properties, corrosion resistance and process stability can be fully highlighted, thereby reflecting the creativity and practical value of the present invention.
[0100] Experiment 1: Mechanical properties test Experimental Description Purpose The mechanical property (yield strength, tensile strength, elongation) advantages of Example 1 compared to Comparative Example 1 were verified, demonstrating the effect of optimizing the ratio of carbon (C) and manganese (Mn) on improving the mechanical properties of steel.
[0101] Experimental procedures 1. Sample Preparation Samples were taken from the steel materials of Example 1 and Comparative Example 1, and the specimens were cut according to standard sizes (length: 100 mm, width: 10 mm, thickness: 2 mm), ensuring that the number of specimens in each group was 5.
[0102] Use an electrolytic polishing machine to finish the surface of the sample, remove surface defects, and ensure that the surface of the sample is smooth.
[0103] 2. Experimental Equipment Universal material testing machine: used for tensile testing, the brand selected is Instron5960.
[0104] Environmental conditions: The experiment was carried out at room temperature of 25℃±1℃.
[0105] 3. Experimental Setup Clamp the sample and adjust the clamp pressure to 50N to ensure that the sample is firmly fixed; The loading rate was set at 10 mm / min, and the load was applied continuously until the specimen broke.
[0106] 4. Data Collection The yield strength (the stress when the sample starts to deform plastically, unit: MPa), tensile strength (maximum stress, unit: MPa) and elongation (elongation of the sample after fracture, unit: %) were tested.
[0107] For each group of samples, record 5 test data and take the average value.
[0108] Experimental data The following is an experimental data table, which records the results of the mechanical properties test of Example 1 and Comparative Example 1.
[0109] Table 1: Mechanical properties test data of Example 1 and Comparative Example 1 Sample No. Yield strength (MPa) Tensile strength(MPa) Elongation(%) Example 1-1 342 481 25.6 Example 1-2 339 475 26.2 Examples 1-3 345 480 26.0 Examples 1-4 340 478 25.8 Examples 1-5 344 482 26.3 average value 342 479 26.0 Comparative Example 1-1 280 402 18.1 Comparative Example 1-2 278 398 18.5 Comparative Examples 1-3 282 400 18.3 Comparative Examples 1-4 277 395 18.0 Comparative Examples 1-5 279 399 18.2 average value 279 399 18.2 Experimental Summary In this experiment, through the mechanical property test of Example 1 and Comparative Example 1, it is found that Example 1 is significantly better than Comparative Example 1 in yield strength, tensile strength and elongation. This performance difference is due to the optimized design of carbon (C) and manganese (Mn) content in the two groups of samples.
[0110] The sample of Example 1 has a carbon content of 0.15% and a manganese content of 1.0%, which achieves stable formation of manganese carbide. The carbides are evenly distributed in the matrix, which enhances the strength and hardness of the steel. At the same time, manganese can refine the grains, improve toughness and plasticity, and ensure a high elongation. However, the sample of Comparative Example 1 has a carbon content of only 0.10% and a manganese content of 0.6%. The carbide formation is insufficient, and the matrix structure cannot be effectively strengthened. In addition, the insufficient manganese content leads to a weak grain refinement effect, which is manifested as a comprehensive decline in mechanical properties.
[0111] This experiment verifies that optimizing the ratio of carbon and manganese is the key to improving the mechanical properties of steel. The uniformity of carbide distribution and the degree of grain refinement directly determine the strength and toughness of steel. The reasonable carbon-manganese ratio in Example 1 not only ensures the improvement of yield strength and tensile strength, but also avoids the risk of increased brittleness, achieving balanced optimization of mechanical properties.
[0112] In addition, the elongation fluctuation range of Example 1 in the test data is smaller than that of Comparative Example 1, which indicates that a reasonable carbon-manganese ratio also enhances the stability of steel performance and is suitable for wide application in practical engineering. This experimental result fully demonstrates the advantages of the technical solution of the present invention in optimizing mechanical properties.
[0113] Experiment 2: Corrosion resistance test Experimental Description Purpose The advantage of Example 2 over Comparative Example 2 in corrosion resistance was verified, and the contribution of the synergistic effect of chromium, nickel and copper to the corrosion resistance was analyzed.
[0114] Experimental procedures 1. Sample Preparation Samples were selected from Example 2 and Comparative Example 2, respectively, with a size of 20 mm×20 mm×2 mm.
[0115] Use polishing sandpaper to gradually grind the surface of the specimen (#600 to #2000) to ensure that the surface of the specimen is smooth.
[0116] The sample was cleaned with anhydrous ethanol for 3 minutes to remove surface grease and impurities, and then placed in a drying oven to dry for later use.
[0117] 2. Experimental Equipment Electrochemical corrosion tests were performed using an electrochemical workstation (CHI660E or equivalent).
[0118] Standard reference electrode: saturated calomel electrode (SCE); auxiliary electrode: platinum sheet.
[0119] 3. Test medium 3.5% NaCl solution, simulating marine environment.
[0120] The solution temperature was kept constant at 25°C ± 1°C.
[0121] 4. Test Setup Open circuit potential (OCP) test: The sample remains stationary in the corrosive medium for 30 minutes, and the change of open circuit potential over time is recorded. The polarization test is started after the potential is stable.
[0122] Polarization curve test: The scanning potential range was set to -1 V to +1 V (relative to SCE), the scanning rate was 1 mV / s, and the polarization curve was recorded.
[0123] Extract the corrosion potential (E_corr, unit: V) and corrosion current density (i_corr, unit: μA / cm 2 ).
[0124] 5. Data Collection Each group of samples was tested 3 times, and the average value was taken and the data distribution was analyzed Experimental data The following are the experimental results, recording the results of Example 2 and Comparative Example 2 in the electrochemical corrosion test.
[0125] Table 2: Corrosion resistance test data of Example 2 and Comparative Example 2 Sample No. Corrosion potential Ecorr(V) <![CDATA[Corrosion current density icorr (μA / cm 2 )]]> Example 2-1 -0.31 2.3 Example 2-2 -0.29 2.1 Example 2-3 -0.33 2.5 Embodiment 2-4 -0.32 2.4 Embodiment 2-5 -0.30 2.2 average value -0.31 2.3 Comparative Example 2-1 -0.45 3.8 Comparative Example 2-2 -0.48 4.2 Comparative Examples 2-3 -0.47 4.0 Comparative Examples 2-4 -0.44 3.9 Comparative Examples 2-5 -0.46 4.1 average value -0.46 4.0 Experimental Summary Through electrochemical corrosion testing, this experiment found that the corrosion potential of Example 2 was significantly higher than that of Comparative Example 2, and the corrosion current density was significantly lower than that of Comparative Example 2, which shows that Example 2 has a significant advantage in corrosion resistance. The increase in corrosion potential reflects the enhancement of the material's corrosion resistance, while the decrease in corrosion current density indicates that the corrosion rate is significantly slowed down.
[0126] In Example 2, excellent corrosion resistance is achieved through the synergistic effect of chromium, nickel and copper. Chromium forms a dense Cr2O3 oxide film on the surface of the steel, which can effectively prevent corrosive media (such as Cl- ions) from penetrating into the matrix and play a barrier protection role; the addition of nickel refines the grains, strengthens the matrix structure, and further improves the corrosion resistance by forming a NiO oxide film; the presence of copper enhances the pitting resistance, especially effectively resisting the corrosion of chloride ions in a 3.5% NaCl solution. In Comparative Example 2, these three elements were not added, the oxide film structure was loose, and the corrosion resistance was greatly reduced, which was manifested as a decrease in corrosion potential and an increase in corrosion current density.
[0127] From the mechanism analysis, it can be seen that the chromium and nickel oxide films form a uniform protective layer on the surface and self-repair the microscopic defects in the corrosion process to prevent the expansion of local corrosion. The copper element further improves the corrosion resistance in the atmosphere and hot and humid environment by changing the surface electrochemical environment and reducing the sensitivity to pitting corrosion. This synergistic effect is the fundamental reason why the corrosion resistance of Example 2 is significantly better than that of Comparative Example 2.
[0128] The experimental results verify that the coordinated addition of chromium, nickel and copper is a key technical solution to significantly improve the corrosion resistance of steel. In particular, under the conditions of marine environment simulation, the corrosion resistance shown in Example 2 can meet the needs of long-term use in actual engineering. By optimizing the chemical composition and improving the mechanism, the steel for rib plates of the present invention overcomes the problem of insufficient corrosion resistance in the prior art and has important practical value.
[0129] Experiment 3: Grain structure observation Experimental Description Purpose The effects of normalizing and tempering heat treatment parameters on the grain structure of the steel were verified, and the differences in grain structure between Example 1 and Comparative Example 3 were analyzed to further demonstrate the effect of optimizing heat treatment parameters on improving mechanical properties.
[0130] Experimental procedures 1. Sample Preparation The samples of Example 1 and Comparative Example 3 were selected, and test blocks of 5 mm×5 mm×5 mm were cut from each group of steel samples along the longitudinal section.
[0131] Use fine sandpaper to gradually sand the specimen (#800 to #4000) to make the surface of the specimen flat and smooth.
[0132] The specimens were immersed in 3% nitric acid alcohol solution for etching for 10 seconds, then rinsed with distilled water and dried with hot air.
[0133] 2. Experimental Equipment The grain structure was observed using an optical microscope at a magnification of 500 times.
[0134] The grain size is evaluated according to GB / T6394-2002 (Method for determination of average grain size of metals).
[0135] 3. Test Methods Five random areas were selected from each sample to record the grain structure and measure the grain size (unit: μm).
[0136] The shape, uniformity and refinement of the grains were compared and observed.
[0137] 4. Data Collection The grain size and grain size of each group of samples were statistically analyzed, and the mean and distribution were recorded.
[0138] Experimental data The following are the experimental results, recording the grain size and grain size measurement results of Example 1 and Comparative Example 3.
[0139] Table 3: Grain structure test data of Example 1 and Comparative Example 3 Experimental Summary The experimental results show that the grain structure of Example 1 is finer and more uniform than that of Comparative Example 3, the grain size (8.1) is significantly higher than that of Comparative Example 3 (5.9), and the average grain size (15.8 μm) is significantly smaller than that of Comparative Example 3 (25.8 μm). This shows that the optimized normalizing and tempering heat treatment parameters effectively promote grain refinement, thereby improving the comprehensive performance of the steel.
[0140] In the normalizing treatment, Example 1 adopts a heating temperature of 950°C and a holding time of 50 minutes to fully homogenize the austenite grains, and forms fine pearlite and ferrite structures in the subsequent air cooling process. However, the normalizing temperature of Comparative Example 3 is set to 1000°C. The excessively high temperature causes the austenite grains to coarsen, resulting in larger grains and poorer uniformity of the microstructure after cooling, which directly affects the mechanical properties of the material.
[0141] In the tempering treatment, Example 1 adopts the optimized parameters of 350°C and 23.5 hours, which stabilizes the ferrite and pearlite structures while reducing the residual stress, further enhancing the toughness and plasticity of the steel. In Comparative Example 3, due to the low tempering temperature (250°C), the residual stress is not released enough, resulting in a large stress concentration in the grain structure, which not only reduces the plasticity, but also may increase the brittleness.
[0142] From a mechanism analysis, grain refinement directly improves the strength and toughness of steel. Small and uniform grain distribution can effectively inhibit the initiation and expansion of cracks and improve the impact resistance of steel. However, coarse grain structure will form stress concentration areas, which can easily lead to local plastic deformation failure and reduce the overall mechanical properties of steel.
[0143] This experiment verifies that the optimization of normalizing and tempering parameters is the key to achieving grain refinement and performance improvement. The grain structure of Example 1 is more suitable for the requirements of high-strength and high-toughness steel in practical engineering applications, while Comparative Example 3 shows significant deficiencies. This experiment further proves the innovation and practicality of the present invention in heat treatment process.
[0144] Experiment 4: Surface oxide film performance test Experimental Description Purpose By comparing Example 2 and Comparative Example 4, the influence of the parameters of low-temperature oxidation treatment (temperature, time, etc.) on the properties of the oxide film on the steel surface (thickness, hardness, peeling performance) is verified, and the effect of the optimized surface treatment process of the present invention on improving corrosion resistance and surface protection is demonstrated.
[0145] Experimental procedures 1. Sample Preparation Samples were selected from Example 2 and Comparative Example 4, respectively, with a size of 10 mm×10 mm×2 mm.
[0146] Use a polishing machine to finish the surface of the sample, clean it, and dry it for later use.
[0147] 2. Test equipment Scanning electron microscope (SEM): used to observe the thickness and uniformity of the surface oxide film.
[0148] Microhardness tester: used to test the surface hardness of oxide film.
[0149] Peeling performance test device: used to evaluate the adhesion of the oxide film, using a sticky roller test.
[0150] 3. Test Methods Oxide film thickness test: Place the sample in the SEM, randomly select 5 areas, and record the thickness of the oxide film (unit: μm).
[0151] Surface hardness test: Use a microhardness tester to load 200g on the sample surface, test each sample 3 times, and take the average value.
[0152] Peeling performance test: The sample is fixed in a sticky roller test device, and after 100 rolling cycles, the peeling of the oxide film is observed (no peeling / partial peeling / complete peeling).
[0153] 4. Data Collection The oxide film thickness, surface hardness and peeling condition were recorded for each group of samples, and the performance differences between the two groups of samples were compared.
[0154] Experimental data The following are the experimental results, recording the data of Example 2 and Comparative Example 4 in the surface oxide film thickness, hardness and peeling performance tests.
[0155] Table 4: Surface oxide film performance test data of Example 2 and Comparative Example 4 Experimental Summary The experimental results show that the oxide film thickness and hardness of Example 2 are significantly better than those of Comparative Example 4, and it also exhibits extremely high adhesion (no peeling) in the peeling performance test. However, the oxide film of Comparative Example 4 is thin and uneven, has a low hardness, and partially or even completely peels off in the peeling test, indicating that the surface protection ability is weak.
[0156] The low temperature oxidation treatment parameters (oxidation temperature 150-200°C, oxidation time 12 hours) adopted in Example 2 formed a uniform and dense Cr2O3 and NiO oxide film on the steel surface. This oxide film is highly stable and can effectively block corrosive media (such as Cl - ions) and enhance the adhesion and toughness of the oxide film through the action of nickel. However, in Comparative Example 4, the oxidation temperature is low (140°C), the oxidation time is insufficient (6 hours), and the oxidation reaction is not completely carried out, resulting in a thin and loose oxide film that cannot play an effective protective role.
[0157] From the perspective of mechanism, the Cr2O3 oxide film formed by chromium has a dense structure under the optimized parameters of the present invention and can provide long-term protection in a corrosive environment; nickel further improves the strength and adhesion of the film by refining the grains and forming a NiO film; copper enhances the film's pitting resistance, making it show extremely high stability in the roller peeling test. However, due to the insufficient oxidation temperature and time in Comparative Example 4, the oxide film cannot form a complete protective layer, and its toughness and strength are greatly reduced.
[0158] The experimental data also show that the oxide film thickness of Example 2 is about 1.76μm and the surface hardness is close to 856HV. This parameter shows an excellent balance in the optimization of steel surface properties and is suitable for steel for ribs exposed to corrosive environments for a long time. In Comparative Example 4, the film thickness is only 0.94μm and the hardness is only 685HV, which are significantly lower than those of Example 2, further proving the necessity of optimizing surface treatment parameters.
[0159] In summary, Experiment 4 verifies the importance of optimizing the low-temperature oxidation treatment parameters (temperature, time), and the surface oxide film performance of Example 2 is significantly better than that of Comparative Example 4, and can provide long-term protection in high humidity and corrosive environments. This result fully demonstrates the innovation and practical value of the present invention in terms of corrosion resistance and surface protection.
[0160] Experiment 5: Practical application performance verification Experimental Description Purpose By simulating the actual wet and hot alternating environment and load conditions, the differences in comprehensive mechanical properties and corrosion resistance between Example 3 and Comparative Example 5 were verified, and the effects of optimized tempering temperature and time on deformation and corrosion properties in engineering applications were analyzed.
[0161] Experimental procedures 1. Sample Preparation Samples of 50 mm×50 mm×3 mm were cut from Example 3 and Comparative Example 5, respectively, and the surfaces were polished with polishing sandpaper until smooth (#400 to #2000), cleaned, and dried for later use.
[0162] 2. Experimental Equipment Hot and humid alternating environment test chamber: used to simulate high heat and humidity environment (temperature 40°C, relative humidity 85%).
[0163] Universal materials testing machine: used to apply a constant tensile load.
[0164] Scanning electron microscope (SEM): used to observe the degree of corrosion on the sample surface.
[0165] 3. Experimental Setup Humidity and heat alternating test: Place the sample in a humidity and heat test chamber with the environmental parameters set at 40°C and 85% relative humidity for 72 hours.
[0166] Load test: After taking the sample out of the wet heat test chamber, place it in a universal material testing machine and apply a static tensile load of 10kN. Continue loading for 72 hours and record the deformation of the sample.
[0167] Corrosion analysis: After the experiment, the corrosion morphology of the sample surface was observed by SEM, and the corrosion area ratio (unit: %) was calculated.
[0168] 4. Data Collection Record the tensile deformation of the specimen under load; Observe the surface corrosion morphology and evaluate the corrosion area.
[0169] Experimental data The following are experimental results, recording the data of Example 3 and Comparative Example 5 in actual application performance tests.
[0170] Table 5: Practical application performance test data of Example 3 and Comparative Example 5 Sample No. Tensile deformation (mm) Surface corrosion area (%) Example 3-1 1.25 8.5 Example 3-2 1.32 8.2 Example 3-3 1.28 8.7 Embodiment 3-4 1.30 8.4 Embodiment 3-5 1.27 8.3 average value 1.28 8.4 Comparative Example 5-1 2.10 15.8 Comparative Example 5-2 2.05 15.2 Comparative Example 5-3 2.15 16.0 Comparative Example 5-4 2.08 15.5 Comparative Example 5-5 2.13 15.9 average value 2.10 15.7 Experimental Summary The experimental results show that Example 3 is significantly better than Comparative Example 5 in terms of tensile deformation and corrosion area. The average tensile deformation of Example 3 is 1.28 mm, while that of Comparative Example 5 is 2.10 mm; the average surface corrosion area of Example 3 is 8.4%, which is only 53.5% of that of Comparative Example 5, showing that Example 3 has better comprehensive performance under engineering environment.
[0171] From the perspective of mechanism analysis, the optimized tempering temperature (500°C) and holding time (2 hours) in Example 3 effectively released the residual stress inside the steel and stabilized the ferrite and pearlite structures, thereby showing a smaller deformation under static load. On the contrary, the tempering temperature of Comparative Example 5 was low (250°C), resulting in insufficient release of residual stress, and the sample showed obvious plastic deformation under tensile load, which directly affected the engineering stability.
[0172] In terms of corrosion performance, the surface low-temperature oxidation treatment of Example 3 generates a dense Cr2O3 and NiO oxide film, which can effectively block Cl- erosion in a hot and humid environment, showing a lower surface corrosion area. However, due to the low oxidation temperature and insufficient time, the oxide film structure of Comparative Example 5 is loose and has poor adhesion, which quickly fails under hot and humid conditions, and the corrosion area increases significantly.
[0173] The experimental data also show that the test results of Example 3 are relatively evenly distributed, indicating that the optimized tempering and surface treatment processes can ensure the stability of steel performance. However, the performance of Comparative Example 5 fluctuates greatly, indicating that the parameters of its heat treatment process are unreasonable and it is difficult to meet the requirements of consistency and reliability in engineering applications.
[0174] This experiment verifies the superior performance of the present invention in an actual hot and humid environment and under static load. Example 3, by virtue of the optimized tempering temperature and surface treatment process, not only significantly reduces the deformation and corrosion area, but also ensures the consistency of performance, which fully proves the practicality and innovation of the present invention in a complex environment.
[0175] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A steel material for rib plate, characterized in that: include: Carbon: 0.12%~0.18% Manganese: 0.8% to 1.2% Silicon: 0.10%~0.25% Phosphorus: ≤0.03% Sulfur: ≤0.025% Aluminum: ≥0.015% Chromium (Cr): 0.06% to 0.1% Nickel (Ni): 0.05%~0.1% Copper (Cu): 0.05%~0.1% The rest is iron: 97.5% to 98.8%.
2. A steel material for rib plates according to claim 1, characterized in that: The content of chromium, nickel and copper is ≤0.3%.
3. A method for producing a rib plate steel material, based on the rib plate steel material according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) Raw material preparation: preparing the chemical composition according to claim 1; (2) Smelting: Using oxygen converter to obtain molten iron; (3) Continuous casting: Molten iron is cast into a slab and then cooled; (4) Normalizing treatment: heating the ingot for normalizing, followed by natural cooling in air; (5) Tempering treatment: heating the ingot for tempering and then cooling; (6) Surface treatment: The ingot is surface treated by low temperature oxidation treatment in a low temperature oxidation environment of 150-200°C for 12 hours.
4. The method for producing a steel material for a rib plate according to claim 3, characterized in that: Aluminum deoxidizer is added during the smelting process, and the added amount of the deoxidizer is 0.02% to 0.05%.
5. The method for producing a steel material for a rib plate according to claim 3, characterized in that: The temperature of the oxygen converter is 1600-1650° C., and the vacuum degassing pressure is 100-110 Pa.
6. The method for producing a steel material for a rib plate according to claim 3, characterized in that: During the continuous casting, the flow rate of molten iron is 1.2-1.5 m / s, and the cooling rate is 2.5-3.5° C. / s.
7. The method for producing a steel material for a rib plate according to claim 3, characterized in that: During the normalizing treatment, the ingot is heated to 900-950° C. and the holding time is 40-60 minutes.
8. The method for producing a steel material for a rib plate according to claim 3, characterized in that: During the tempering treatment, the ingot is heated to 300-500° C., kept at this temperature for 23-23.5 hours, and cooled at a rate of 0.5-1.5° C. / min.
9. The method for producing a steel material for a rib plate according to claim 3, characterized in that: The casting slab is surface treated using a low temperature oxidation furnace, the surface treatment comprising the following steps: Clean the surface of the ingot after tempering to remove grease, oxide scale and impurities on the surface; Placing the cleaned ingot into the heating zone of the low temperature oxidation furnace; Connect oxygen and start the low-temperature oxidation furnace, raise the temperature in the furnace to 150-200°C at a heating rate of 3-5°C / min, maintain this temperature for oxidation treatment for 11.5-12.5 hours, and continuously supply oxygen during this period, with an oxygen flow rate of 10-20L / min and an oxygen purity of ≥99.9%; After completion, turn off the heating system, control the cooling rate to 2-5℃ / min and cool to room temperature; After cooling to room temperature, the surface of the ingot is purged to remove floating ash and loose oxide particles.
10. The method for producing a steel material for a rib plate according to claim 9, characterized in that: When the ingots are placed, a gap of 20 to 30 mm is left between two adjacent ingots for oxygen circulation.